The Efficiency of Using Visual Elements in Developing Some Listening Skills among University Students : A Case Study Karary University-College of Maritime Studies - Mohy Aldin, Amin Mohamed Ahmed; Omer, Yasser Othman Jamaan (جامعة البحر الأحمر, 2018)
The aim of this investigation is to examine the role of visual elements in foreign language listening comprehension when visual elements are used as a mode of presentation. To achieve this purpose, three tools were used. Firstly, a list of listening skills was collected from literature to determine the necessary listening skills needed by third academic term at Karary University - College of Maritime Studies. Secondly, a pre and post tests were prepared and programmed to measure the effectiveness of the software in developing some listening skills. They were administered at the beginning and end of the experiment to measure students› listening skills. Thirdly, a multi-media software was designed, programmed, and administered by the researchers for developing students› listening skills. The sample of the research included twenty students of third academic term at College of Maritime Studies. They were randomly selected to be included in the experimental group (ten students) and the control group (ten students) and randomly assigned to the two groups. Findings of the research revealed that the software designed for the purpose of developing some listening skills has been effective in the development of specific listening skills for the third academic term College of Maritime Studies. The test›s results reveal statistically significant differences between the post-test mean scores in all listening skills; namely, listening for the gist, listening for specific information, listening to guess the meaning of unfamiliar words from context, and listening to use the context to make predictions. The total scores are in favor of the experimental group. Important recommendations of the study are: multimedia technology would facilitate the effective development of listening skills more than the traditional tools of cassettes, and teachers should consider brain-storming, discussion as an introduction to the topics, focus on stress and intonation, utilization of background knowledge, motivation, and introduction of new words.
تهدف هذه الدراسة لاختبار الدور الذي تلعبه الوسائل المساعدة المرئية عند استخدامها كطريقة لعرض مهارة الاستماع للغة الأجنبية. لتحقيق غاية البحث تم استخدام ثلاث أدوات. أولا: تم جمع قائمة في مهارات الاستماع من الكتابات المختلفة لتحديد مهارات الاستماع الضرورية لطلاب الفصل الدراسي الثالث بجامعة كرري -كلية الدراسات البحرية. ثانيا: تم تجهيز اختبارات قبلية وبعدية وبرمجتها لقياس فاعليتها في تنمية بعض مهارات الاستماع والتي تم تنفيذها في بداية ونهاية التجربة لقياس مهارات الاستماع لدى الطلاب. ثالثا: تم تصميم وبرمجة وتنفيذ برنامج متعدد الوسائط بواسطة الباحثان لتنمية مهارة الاستماع لدى الطلاب. تضمنت عينة البحث عشرون طالبا بالفصل الدراسي الثالث بكلية الدراسات البحرية. تم اختيار الطلاب بطريقة عشوائية لتضم المجموعة التجريبية (عشرة طلاب) والمجموعة الضابطة (عشرة طلاب) وتم التعيين للمجموعتين بصورة عشوائية. أظهرت نتائج البحث بأن البرنامج المصمم لغرض تطوير بعض مهارات الاستماع أظهر فعاليته في تطوير المهارات الخاصة بالاستماع لطلاب الفصل الدراسي الثالث بكلية الدراسات البحرية. نتائج الاختبارات أظهرت اختلافات إحصائية مهمة بين متوسط الدرجات للامتحان القبلي في كل مهارات الاستماع أي: الاستماع إلى الفكرة العامة للنص، الاستماع لمعلومات محددة، الاستماع لتخمين المعنى لكلمات غير مألوفة من سياق الكلام، والاستماع لاستخدام القرينة للتنبؤ. مجموع الدرجات في صالح المجموعة التجريبية. أهم توصيات الدراسة هي: أن تكنولوجيا الوسائط المتعددة ستسهل التطوير الفعال لمهارات الاستماع أكثر من الوسائل التقليدية كأشرطة التسجيل الصوتية. ينبغي على المعلمين الأخذ في الاعتبار العصف الذهني والنقاش كتمهيد للموضوعات والتركيز على النبرة الصوتية وارتفاع وانخفاض طبقة الصوت أثناء التحدث والاستفادة من خلفية المعرفة والدافعية وإدخال كلمات جديدة.
Keywords: اللغة الإنجليزية -- اللغة الأجنبية -- مهارة الاستماع -- الوسائل المساعدة المرئية